Collectivistic coping styles and mental well-being of college students in Malaysia - Leow, Serena Wai Yee *; Leow, Kenneth; Wong, Evelyn Mei Ling (psychologyandeducation.net, 2019)
The aim of this study was to investigate the relationship between depressive symptoms and collectivistic coping styles (CCS) among Malaysian college students. A total of 176 (130 females, 46 males) students from a university in Selangor, Malaysia, completed measures of CCS and mental well-being. Data were analyzed using correlation coefficient and regression analysis. Results revealed a significant positive relationship between mental well-being and CCS. Specifically, regression analysis showed that acceptance, reframing, and striving (ARS), family support (FS), and private emotional outlet (PEO) were significant predictors of mental well-being among college students in Malaysia. These dimensions of collectivistic coping strategies were particularly useful to mitigate stressors among college students in Malaysia.